A Multimodal Social Semiotic Analysis of Typography and Layout in ‘’Alexander Master’s Novel Stuart: A Life Backwards’’ - Gheni, Ali Abdulelah; Al-Hindawi, Fareed Hameed (Journal of Ecohumanism, 2024)
The output of multimodal texts has increased over the past 20 years due to advances in technology and culture, which has accelerated the demand for tackling multimodal additional semiotic modes for meaning making, such as typography, layout ,visual images, colour, etc. The theory of multimodality, as supposed by Kress and Van Leeuwen (2001–2006), Baldry and Thibaut (2006), is applied to a potential framework for the analysis of multimodal novels that use not only wording structure but also many semiotic modes in the formation of meaning. The social approach to multimodality, in brief, is based on Halliday’s linguistic description and adhered to the multimodal assumption that "mutual propositions are employed and worked together in various modes" (Kress and Leeuwen,2002:3). Thus, Kress and Van Leeuwen (1996:39), in their book ‘’Reading Images’’ investigate the level for which the underlying theories of Halliday’s framework to language are feasible and applicative to visual communicative management, and they create a visual system that mostly makes use of Halliday’s principles and concepts. The study is concerned with the investigation of a multimodal analysis of the multiple elements of various modes of typographic devices, and layout design used in the selected novel. This selected text ‘’Stuart: A Life Backwards’’ is a multimodal novel since the writer Masters does not rely on linguistic verbal tools, he extends them to incorporate a variety of visual semiotic modes and graphic communicative elements that will intensify his understanding of storytelling and narrative development. The study has shown that an extension to the mode of wording formation is performed in the multimodal analysis by incorporating more multimodal tackling features of typographic principles and layout framing devices in creating an appropriate comprehensive meaning construction in Masters’ selected narration.